Jasmonate-Responsive Transcription Factors NnWRKY70a and NnWRKY70b Positively Regulate Benzylisoquinoline Alkaloid Biosynthesis in Lotus (Nelumbo nucifera) - Li, Jing; Li, Yi; Dang, Mingjing; Li, Shang; Chen, Simeng; Liu, Ruizhen; Zhang, Zeyu; Li, Guoqian; Zhang, Minghua; Yang, Dong; Yang, Mei; Liu, Yanling; et al. (Frontiers in Plant Science, 2022)
Lotus (Nelumbo nucifera) is a large aquatic plant that accumulates pharmacologically significant benzylisoquinoline alkaloids (BIAs). However, little is known about their biosynthesis and regulation. Here, we show that the two group III WRKY transcription factors (TFs), NnWRKY70a and NnWRKY70b, positively regulate the BIA biosynthesis in lotus. Both NnWRKY70s are jasmonic acid (JA) responsive, with their expression profiles highly correlated to the BIA concentration and BIA pathway gene expression. A dual-luciferase assay showed that NnWRKY70a could transactivate the NnTYDC promoter, whereas NnWRKY70b could activate promoters of the three BIA structural genes, including NnTYDC, NnCYP80G, and Nn7OMT. In addition, the transient overexpression of NnWRKY70a and NnWRKY70b in lotus petals significantly elevated the BIA alkaloid concentrations. Notably, NnWRKY70b seems to be a stronger BIA biosynthesis regulator, because it dramatically induced more BIA structural gene expressions and BIA accumulation than NnWRKY70a. A yeast two-hybrid assay further revealed that NnWRKY70b physically interacted with NnJAZ1 and two other group III WRKY TFs (NnWRKY53b and NnWRKY70a), suggesting that it may cooperate with the other group III WRKYs to adjust the lotus BIA biosynthesis via the JA-signaling pathway. To illustrate the mechanism underlying NnWRKY70b-mediated BIA regulation in the lotus, a simplified model is proposed. Our study provides useful insights into the regulatory roles of WRKY TFs in the biosynthesis of secondary metabolites.